INFLUENCE OF WORK ENVIRONMENT AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE AT THE REGIONAL SECRETARIAT OFFICE OF KOTABARU DISTRICT, SOUTH KALIMANTAN PROVINCE - Nurul Fitriah; Meiske Kristin Lumanauw (SEAN Institute, 2020)
Performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Meanwhile, improving performance is something that is desired by both the employer and the workers. To achieve good performance, work environment and compensation are very influential. In addition, the motivation obtained by employees is an important aspect, because it has an impact on better performance. T his study aims to determine the effect of work environment, compensation and job satisfaction on performance. The population in this study were all employees at the Regional Secretariat Office of Kotabaru Regency, Province South Kalimantan totaling 60 people. The researcher uses a saturated sampling technique . The data analysis in this study used the path analysis model, because of the intervening variables . The value of this study indicates that the work environment and compensation have a significant positive effect on motivation. Work environment, compensation and work motivation are proven to have a significant positive effect on employee performance.